2018
DOI: 10.21608/jacb.2018.35242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of some Egyptian Sheep Populations Using Microsatellite and Protein Markers

Abstract: Three Egyptian sheep populations, collected from three geographically isolated regions namely Siwa, El-Dakhla and El-Farafra oases of the Egyptian western desert, were investigated using six polymorphic microsatellite markers and electrophoretic protein by SDS-PAGE. Six polymorphic microsatellite markers and electrophoretic protein were used to reveal that the genetic diversity, conduct genetic structure and assignment of microsatellite. The results indicated that; one hundred and five alleles were detected; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…and Beetal breed has band of 36.5 kDa). El-Hamamsy et al (2018) reported that the Siwa had 20 protein bands that MW ranged from 17 to 269 KDa, the homogeneity of individual Siwa samples was 30%. El-Dakhla population had 23 protein bands that ranged from 17 to 283KDa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Beetal breed has band of 36.5 kDa). El-Hamamsy et al (2018) reported that the Siwa had 20 protein bands that MW ranged from 17 to 269 KDa, the homogeneity of individual Siwa samples was 30%. El-Dakhla population had 23 protein bands that ranged from 17 to 283KDa.…”
Section: Discussionmentioning
confidence: 99%
“…A polyacrylamide gel electrophoresis is a valuable tool for establishing the quantitative distribution of proteins in goats (Shauket et al, 1998;Simplício et al, 2017) illustrated that the detection and quantification of acute-phase proteins by SDSP-AGE was useful and reliable as a complementary test in goats. The protein profile can be used as a marker depending on the presence or absence bands, band intensity, molecular weight and relative front values (El-Hamamsy et al, 2018). In addition, the coding sequences of bovine myostatin in two double-muscled cattle's have been identified, as well as nine other vertebrate species' myostatin sequences (Belgian Blue and Piedmontese) (Mcpherron et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…According to a literature survey, several papers concerning its morphological characterization (Mousa et al, 2006;Galal, 2007;Elbeltagy, 2012;Elshazly and Youngs, 2019). Moreover, only one available molecular study was performed by El-Hamamsy et al (2018). They characterized three Egyptian sheep populations, collected from Siwa, El-Dakhla and El-Farafra Oases of the Egyptian Western Desert, using microsatellite marker and electrophoretic protein.…”
Section: Introductionmentioning
confidence: 99%